A Survey on Face Recognition Based Attendance System and Its Techniques - Chilme, Pravin Panditrao; Jaffarkhan, Pathan Naserkhan (International Journal of Computer Sciences and Engineering, 2019)
Face recognition is a rising and important research area for many years. Numerous motives raised from the automatic recognitions and surveillance structures, the need for the human visual device on face reputation, and the modeling of human-computer interface, and so on. Those researches involve understanding and researchers from disciplines like neuroscience, psychology, pc vision, pattern recognition, picture processing, and system gaining knowledge of, etc. A set of researchers came into life to type out the specific elements like illumination, expression, scale, pose, and advantage the first-class popularity charge, when there is nevertheless no strong method against out of control realistic cases which may additionally contain types of elements. A facial recognition system is a computer application that has the capability of locating a person from a digital image or a video body from a video source. The most important part of spotting someone is his or her face. With the help of photograph processing strategies, we can explore the traits appearances of someone. In the old approach that is utilized in colleges and faculties, it`s far there that the professor calls the student call and then the attendance for the scholars marked. For the images which are stored inside the database, we follow a machine set of rules which incorporates steps consisting of, histogram classification, noise elimination, face detection, and face recognition techniques. So by utilizing those steps, we come across the faces after which examine it with the database. The attendance gets marked automatically if the machine recognizes the faces. This paper presents a comparative examine of several strategies of face reputation systems.